How informative is qualitative management earnings guidance?. (June 2018) - Hart, Matthew
Abstract: In this paper I examine the information content of qualitative management earnings guidance relative to quantitative guidance. Hirst et al. (2008) note that managers may issue earnings forecasts in either qualitative or quantitative forms. Prior research on the consequences of forecast form has focused primarily on different forms of quantitative earnings guidance. This work either finds no effect of forecast form or that more precise guidance is more credible or informative. Using a sample of 14, 468 quantitative EPS forecasts and 1265 qualitative EPS forecasts, I find that qualitative bad news forecasts are more informative to investors (i.e., have a stronger market reaction) and analysts (i.e., have larger earnings revisions) than quantitative bad news forecasts. By way of an explanation, I find that qualitative bad news forecasts are more accurate ex post than quantitative bad news forecasts. The results indicate that in the case of bad news EPS forecasts, the qualitative forecast form itself provides a signal to market participants, above and beyond the actual earnings expectation, that the forthcoming earnings surprise may be more negative than anticipated, and that investors and analysts react accordingly.